TEST OF TYROSINASE ENZYME INHIBITOR ACTIVITY OF BIDARA ARAB LEAVES ETHANOL EXTRACT (ZIZIPHUS SPINA-CHRISTI L.) BY IN VITRO - Dini Rizky Purnamasari (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2020)
Bidara Arab (Ziziphus spina-christi L.) is one of the tropical trees that is very useful and is often called a versatile plant. Several studies have proven that this plant is used as an antimicrobial, antidiabetic, antipireutic, anticancer and also has the potential to inhibit the enzyme tyrosinase. Kojic acid is one of the agents used to inhibit the tyrosinase enzyme so that it prevents hyperpigmentation. This study aims to determine the inhibitory activity of the tyrosinase enzyme from the ethanol extract of Bidara Arab leaves (Ziziphus spina-christi L.) in vitro. The method used in extraction is the maceration method using 70% ethanol until thick extract is obtained. Tests were carried out using 2 substrate namely L-Tyrosine and L-DOPA, ethanol extract of Bidara Arab leaves with concentrations of 10000, 8000, 4000, 2000 and 1000 μg / mL and kojat acid as positive controls and then measured absorption using microplate reader at wavelength 510 nm. The results showed that the Bidara Arab ethanol extract had tyrosinase inhibitor activity with IC50 values of 5364,186 in L-Tyrosine and 5568,362 in L-DOPA. Keywords: Bidara Arab; Kojic Acid; Tyrosinase Enzyme; Hyperpigmentation; Microplate reader